2005
DOI: 10.4049/jimmunol.174.11.7368
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Anti-IL-10 Antibody Blocks the Protective Effect of Tapeworm Infection in a Murine Model of Chemically Induced Colitis

Abstract: There is increasing evidence that parasitic helminth infection has the ability to ameliorate other disease conditions. In this study the ability of the rat tapeworm, Hymenolepis diminuta, to modulate dinitrobenzene sulfonic acid (DNBS)-induced colitis in mice is assessed. Mice receiving DNBS (3 mg intrarectally) developed colitis by 72 h after treatment. Mice infected 8 days before DNBS with five H. diminuta larvae were significantly protected from the colitis, as gauged by reduced clinical disease, histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
213
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 151 publications
(227 citation statements)
references
References 48 publications
14
213
0
Order By: Relevance
“…Thus, in the presence of the physiological regulatory circuits, reduced IL-10 allows p110d-deficient T cells to develop a predominant, unopposed type 1 response. This interpretation is consistent with the previously described sporadic inflammatory bowel disease (IBD) phenotype occurring in older p110d-inactivated mice [11], since IBD is known to involve deregulated Th1 responses and is opposed by IL-10 [25].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, in the presence of the physiological regulatory circuits, reduced IL-10 allows p110d-deficient T cells to develop a predominant, unopposed type 1 response. This interpretation is consistent with the previously described sporadic inflammatory bowel disease (IBD) phenotype occurring in older p110d-inactivated mice [11], since IBD is known to involve deregulated Th1 responses and is opposed by IL-10 [25].…”
Section: Discussionsupporting
confidence: 92%
“…Fur was removed from the knees of anesthetized mice using hair removal lotion (Nair; Church & Dwight Canada), and CFA (Sigma) was injected into the articular joint space via a 30G1/2-gauge needle, as previously described (14,15 (9). Additional mice were gavaged with 10 H diminuta cysticercoids that had been destroyed by sonication and boiled for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…1 Collectively, these studies have shown that as a consequence of the host response to infection with helminth parasites, there is mobilization of transforming growth factor (TGF)-␤, interleukin (IL)-10, Foxp3 ϩ regulatory T cells, alternatively activated macrophages, and inhibition of IL-17-and interferon (IFN)-␥-driven events: one, or a combination, of these events could block the development of autoimmune and inflammatory disorders. [2][3][4][5][6][7] These findings have been complemented by intriguing data suggesting that infection with viable parasitic nematodes could be a treatment for patients with inflammatory bowel disease (IBD) 8 or asthma, 9 whose condition is not managed by conventional therapies.…”
mentioning
confidence: 87%
“…delivery in accordance with our earlier study and for comparisons with the DNBS model of colitis. 3 Experiments conformed to the Canadian guidelines for animal welfare.…”
Section: Mice and Induction Of Colitismentioning
confidence: 99%
See 1 more Smart Citation